A plausible causal link between antiretroviral therapy and increased blood pressure in a sub-Saharan African setting: A propensity score-matched analysis. (1st October 2016) - Nduka, Chidozie U.; Stranges, Saverio; Bloomfield, Gerald S.; Kimani, Peter K.; Achinge, Godwin; Malu, Abraham O.; Uthman, Olalekan A.
Abstract: Background: The transition from association to causation could represent a fundamental step for taking preventive action against hypertension and its complications, especially among HIV-infected persons on antiretroviral therapy in sub-Saharan African countries. Methods: 406 consecutive HIV-infected adults attending a tertiary HIV clinic in semi-urban Nigeria were prospectively recruited between August and November 2014. These participants were stratified by antiretroviral treatment status. A propensity score matching model was fitted to examine the causal average treatment effects on the treated (ATT) of antiretroviral therapy on blood pressure. Propensity score matching entailed using nearest neighbour matching with a calliper width of 0.2 to achieve similarity in the baseline characteristics between participants naïve and exposed to antiretroviral therapy. Results: Matching HIV-infected patients naïve and exposed to antiretroviral therapy on the propensity score yielded a total of 303 participants ― 229 antiretroviral-exposed and 74 antiretroviral-naïve ― matched without any residual differences in the baseline characteristics between both groups of patients. In this propensity score-matched sample, the estimated ATT for the effects of antiretroviral therapy on systolic (7.85 mm Hg, 95% CI 3.72 to 15.68) and diastolic blood pressure (7.45 mm Hg, 95% CI 4.99 to 13.61) were statistically significant ( P < 0.001 for each). Conclusions: There is a high probability that the epidemiological association between antiretroviral therapy and increased blood pressure be causal in nature among people living with HIV in sub-Saharan African settings. HIV-infected patients commencing antiretroviral treatment in these settings may require regular hypertension screening and other cardiovascular risk assessments.